Effect of time and duration of untreated psychosis on cognitive and social functioning in Chinese patients with first-episode schizophrenia: A 1-year study. (May 2015) - Heeramun-Aubeeluck, Anisha; Liu, Na; Fischer, Felix; Huang, Nan; Chen, Fazhan; He, Leiying; Yang, Chengqing; Luo, Yanli; Lu, Zheng
Abstract Background: Duration of untreated psychosis (DUP) is believed to exert a deleterious effect on cognitive and social function. However, to date, results remain inconclusive. Aims: To investigate the effect of time and DUP on cognitive and social functioning in first-episode schizophrenia (FES) subjects in Shanghai, China. Methods: FES patients were subjected to a comprehensive neuropsychological battery, the Personal and Social Performance scale (PSP) and the Positive and Negative Symptoms Scale (PANSS) at baseline, 6 month and 1 year. DUP was defined as the time from onset of first psychotic symptoms to first contact made with psychiatric services. Results: Though the rate of non-completers in our observational study was relatively high (40%), we did not find any significant differences between the completers and non-completers (P-values > 0.05). Significant impairments in verbal learning and memory and executive function were noted over the course of 1 year. Meanwhile, social function improved significantly over the course of 1 year. Although, DUP did not share any significant relationship with cognitive or social function the effect estimate (range: − 0.03 to 0.02) of an increase of 1 month in DUP was clinically non-negligible in this study. Conclusions: In Chinese FES patients, the longitudinal course of cognitive function tends to worsen in verbal learning and memory, executive function and motor speed, while that of social function tends to improve. DUP was not found to be associated with cognitive or social deterioration in Chinese FES.